2018
DOI: 10.1590/fst.09217
|View full text |Cite
|
Sign up to set email alerts
|

Performance of low-fat beef burger with added soluble and insoluble dietary fibers

Abstract: Onulin, fructooligosaccharide, oat fiber and wheat fiber were added at 3 and 6% level in low-fat beef burger and their performances were evaluated. The low-fat beef burgers were submitted to cooking losses, objective color, texture profile, TBARS value, pH, microbiological and sensory evaluations. FR3, FR6, ON3 e ON6 showed no difference from the control to yield. Hardness values increased in DF6, WF3 and WF6 and it was similar to control. WF6 was the lowest score for the overall acceptance. Higher yield and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 33 publications
2
13
0
7
Order By: Relevance
“…The incorporation of only one type of dietary fiber in the cooked Paio sausage (T9-3% of inulin; T11-3% of oat fiber) showed a reduction (P < 0.05) in L* (Table 5) compromising the lightness value. The addition of Fructooligosaccharide and inulin at 3% and 6% caused a reduction in the lightness value in low-fat beef burger (Bis-Souza et al, 2018). Dther study reported a decreased of lightness with the increase in chia flour addition in chicken nuggets (Barros et al, 2018).…”
Section: Instrumental Colormentioning
confidence: 93%
“…The incorporation of only one type of dietary fiber in the cooked Paio sausage (T9-3% of inulin; T11-3% of oat fiber) showed a reduction (P < 0.05) in L* (Table 5) compromising the lightness value. The addition of Fructooligosaccharide and inulin at 3% and 6% caused a reduction in the lightness value in low-fat beef burger (Bis-Souza et al, 2018). Dther study reported a decreased of lightness with the increase in chia flour addition in chicken nuggets (Barros et al, 2018).…”
Section: Instrumental Colormentioning
confidence: 93%
“…Several studies have shown the possibility of replacing fat with dietary fibre in meat products with good sensory acceptance (Huang et al, 2011;Grizotto et al, 2012;Schmiele et al, 2015;Talukder, 2015;Barretto et al, 2015;Borrajo et al, 2016;Carvalho et al, 2017;Bis-Souza et al, 2018;Zhao et al, 2018;Abbasi et al, 2019), increasing the intake of this component in the diet. These ingredients can contribute giving technological benefits in meat products in order to improve their nutritional and sensory characteristics (Méndez-Zamora et al, 2015;Paglarini et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…As propriedades tecnológicas e efeitos fisiológicos são distintos para a fibra alimentar insolúvel e solúvel (Bis- Souza, Henck & Barretto, 2018). No entanto, no organismo humano, tanto as fibras solúveis quanto as insolúveis contribuem para aumentar a saciedade, evitar as dores causadas pela fome e reduzir o ganho de peso (Suharoschi et al, 2019).…”
Section: Fibras Alimentares E Suas Aplicaçõesunclassified
“…A quantidade de moléculas de frutose que constitui a inulina e o fruto-oligossacarídeo é o que diferencia essas duas fibras (Rosa & Cruz, 2017). Ambas são solúveis em água e beneficiam a saúde do ser humano, contribuindo para a redução da concentração de colesterol LDL no sangue evitando o progresso de doenças crônicas não transmissíveis; além de promover o crescimento e a atividade de bactérias benéficas no intestino humano, sendo denominadas de prebióticos (Bis- Souza et al, 2018).…”
Section: Rosa E Cruzunclassified